NONLINEAR FINITE ELEMENT ANALYSIS OF THIN-WALLED STEEL TUBE AND CONCRETE-FILLED STEEL TUBE (CFT) COLUMNS - AWADH AHMED BA RAHMA, AHMED (IRC, 2016)
Thin-walled structural members have the ability to resist high tension and bending forces. At the same time, steel members can carry the compression force. For those reasons the engineers started extensively using the cold-formed steel members in construction industry, especially in light-weight buildings. Physical experiments are relatively time consuming. Therefore, finite element analysis (FEA) plays a significant part in practices of engineering. In the finite element model, measuring the primary geometric insufficiency, dimensions of cross-section and properties of materials must be taken in account. In this research a non-linear FEM (included nonlinearities of material and geometric) has been used. The FEM results that obtained from ANSYS.15 software were compared against the results that obtained from experiments or codes-design. The results of failure modes and ultimate loads for columns have been predicted and obtained by using finite element model of ANSYS.15 software. Also, the parametric study of cross-section has been used in analysis of FEM for columns with different heights. The strengths of channel columns that obtained from experiment have been compared against the results that calculated using BS5950 code and obtained from ANSYS.15. On the other hand, the strengths of hollow circular and box columns that obtained from ANSYS.15 software have been compared against the results that calculated using BS5950 code. Also concrete is considered as brittle material. So, an application of thin walled steel jacketing around the concrete is a best solution with a view to improve and increase the ductility and strength of concrete. The study of FEA is used to check the strengths and buckling behavior of fixed-ended thin walled plain hollow circular, box and channel cross-sections columns and also concrete-filled steel tube (CFT) column. Also to strengthen the concrete columns by applying thin walled steel jacketing around columns. The results also showed that application of steel tube jacketing in CFT composite columns mitigates the concrete cracks and also increases the stiffness and strength of the columns.